2021
DOI: 10.1097/md.0000000000024171
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament injury patterns and their relationship to fatigue and physical fitness levels – a cross-sectional study

Abstract: Anterior cruciate ligament (ACL) injury is one of the most common knee injuries that leads to many consequences such as early osteoarthritis and knee joint instability. To explore the association of the types of ACL tear (complete and partial) and side of injury (dominant vs nondominate) with types of playing surfaces, sports, shoes, and mechanism of injuries as well as to determine whether higher levels of fatigue and physical fitness are risk factors for complete ACL tear. This cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To uphold a rigorous standard of precision, this study exclusively incorporated the literature written in English. The possibility of a thorough Journal for Re Attach Therapy and Developmental Diversities eISSN: 2589-7799 2023 August; 6 (8s): 867-872 examination of publications is enhanced when they are published in English, which is widely recognized as the international language of choice [1]. The utilization of materials written in languages other than English has the potential to produce false information [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To uphold a rigorous standard of precision, this study exclusively incorporated the literature written in English. The possibility of a thorough Journal for Re Attach Therapy and Developmental Diversities eISSN: 2589-7799 2023 August; 6 (8s): 867-872 examination of publications is enhanced when they are published in English, which is widely recognized as the international language of choice [1]. The utilization of materials written in languages other than English has the potential to produce false information [6].…”
Section: Methodsmentioning
confidence: 99%
“…It employs scientifically established treatments such as resistance training with heavy external loads to promote muscle mass. [1]. However, major problems arise in specific patient populations.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Injuries usually evolve from unexpected alteration in the direction, or sudden deceleration while running that can occur in sports involving pivoting actions like basketball, football, and gymnastics. 7 Unfavorable consequences of ACL injury include knee joint instability, meniscal and chondral destruction, and higher incidence of osteoarthritis. 8 To retrieve the stability of the knee joint, ACL reconstruction (ACLR) is widely accepted as the gold-standard treatment for active people.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, motor balance function is also an important factor [ 6 , 7 ]. Recent studies have shown that visual feedback is essential to determine balance, and the postural stability of individuals with low vision is worse than that with normal vision [ 8 ]. The influence of dim light can also cause visual changes in gait speed, playing football and trunk control parameters.…”
Section: Introductionmentioning
confidence: 99%